2017
DOI: 10.1177/0379572117724545
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Level Associates With Handgrip Muscle Strength Among Ethiopian Schoolchildren: A Cross-Sectional Study

Abstract: Serum 25(OH)D levels had significant positive association with handgrip strength of Ethiopian schoolchildren. The results imply the need for incorporating school nutrition education on consumption of foods rich in important nutrients including vitamin D-rich foods in the school curricula and also enhancing behavioral change communication toward exposure to sunlight in the school to produce adequate vitamin D. Further longitudinal study involving a larger sample is recommended to confirm the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…These findings are in line with another study conducted in healthy children and adolescents [29]. A study showed that handgrip strength was positively associated with serum levels of vitamin D [30]. It has also been observed that handgrip strength is a predictive factor for bone density in female adolescents and that having a low level of strength indicates poor health in terms of bone density [31].…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in line with another study conducted in healthy children and adolescents [29]. A study showed that handgrip strength was positively associated with serum levels of vitamin D [30]. It has also been observed that handgrip strength is a predictive factor for bone density in female adolescents and that having a low level of strength indicates poor health in terms of bone density [31].…”
Section: Discussionsupporting
confidence: 89%
“…There is still lack of knowledge in terms of the role of vitamin D for upper limb muscle strength in the general population. The studies of Haslam et al [50] and Wang et al [51] showed that vitamin D de ciency is related to loss of hand grip strength in the older population and there is evidence that vitamin D also has a key role in younger age groups for upper limb muscle strength [6,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies on vitamin D and muscle strength in children and adolescents have shown positive results in four (15)(16)(17)(18), and negative results in one (19). Taken together, the large RCT meta-analysis in adults and the majority of observational studies in different populations favor an impact of vitamin D on muscle strength.…”
Section: B Vitamin Dmentioning
confidence: 96%
“…In our interpretation, weight became a stronger expression for muscle and bone mass after adjusting for body fat percentage, analogous to lean body mass, or fat free mass. The impact of body fat percentage has only been investigated in a few other studies in children with similar results (7,16). In further studies on muscular strength in children, we recommend adjustment with a measure of body fat in addition to weight and height and stratification by sex.…”
Section: A Hand Grip and Explanatory Variablesmentioning
confidence: 99%
See 1 more Smart Citation